2000
DOI: 10.1111/j.1530-0277.2000.tb04596.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Are Not Adults: Developmental Considerations in Alcohol Users

Abstract: Much of the work in adolescent substance abuse assessment and treatment has been a direct transport from tools and modalities used in adult substance use populations. There was a consensus among symposium participants that developmental issues are important in assessment, evaluation, and treatment of adolescents with substance use disorders. These issues directly impact outcome at all levels. Presentations from the symposium may be helpful for conceptualizing the problems of adolescent substance use as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(90 citation statements)
references
References 29 publications
5
84
1
Order By: Relevance
“…Yet, there are notable differences between adolescent and adult drinking patterns (Clark, 2004;Colby et al, 2004). Comparing adolescents and adults, Deas et al (2000) found that adolescents drink less frequently than adults and have fewer physiological symptoms of alcohol dependence, but consumed similar quantities of alcohol per occasion.…”
Section: Substance Use Disordersmentioning
confidence: 96%
“…Yet, there are notable differences between adolescent and adult drinking patterns (Clark, 2004;Colby et al, 2004). Comparing adolescents and adults, Deas et al (2000) found that adolescents drink less frequently than adults and have fewer physiological symptoms of alcohol dependence, but consumed similar quantities of alcohol per occasion.…”
Section: Substance Use Disordersmentioning
confidence: 96%
“…Ellickson, McGuigan, Adams, Bell, and Hays (1996) found in their study with 4390 high school students that high alcohol consumption only identifies half of the students labeled as "at-risk misusers" and conclude that teenage alcohol misuse needs to include the three dimensions: "high-risk drinking," "alcohol-related problems," and "high consumption." Furthermore, regular alcohol use was found to be less common in adolescents (Deas, Riggs, Langenbucher, Goldman, & Brown, 2000;Wechsler, Kuo, Lee, & Dowdall, 2000) and to be not useful for identification of risky drinkers in this age group (Reboussin, Song, Shrestha, Lohman, & Wolfson, 2006). In general, measures commonly used to identify adult alcohol misuse such as one-dimensional quantity and frequency measures were found not to be applicable for adolescent populations, because adolescent problem drinking is better captured by drinking patterns (Ellickson et al, 1996;Townshend & Duka, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…Adolescents are also more likely to be referred to treatment by the criminal justice system compared with adults (Substance Abuse and Mental Health Services Administration, Office of Applied Studies, 2001), which may influence motivation to change substance use behavior. Further, adolescents' typically shorter history of substance use and lower severity of drug problems compared with adults (Deas, Riggs, Langenbucher, Goldman, & Brown, 2000) may impact longer term clinical course. Some longer term studies have begun to be reported in the literature of drug-abusing youth.…”
Section: Introductionmentioning
confidence: 98%